1994
DOI: 10.1128/iai.62.5.1975-1981.1994
|View full text |Cite
|
Sign up to set email alerts
|

Production of tumor necrosis factor alpha in human leukocytes stimulated by Cryptococcus neoformans

Abstract: Tumor necrosis factor alpha (TNF-ox) is a key mediator of inflammation and may promote human immunodeficiency virus replication in latently infected cells. Since cryptococcosis often is associated with aberrations in the host inflammatory response and occurs preferentially in persons with AIDS, we defined the conditions under which human leukocytes produce TNF-a when stimulated by Cryptococcus neoformans. Peripheral blood mononuclear cells (PBMC) produced comparable amounts of TNF-ot following stimulation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
63
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 28 publications
13
63
0
Order By: Relevance
“…125 The presence of complement is a prerequisite for TNF-a induction. 125,126 Opsonised C. neoformans also provokes the release of TNF-a from DC. 107 The produced TNF-a efficiently supports ingestion of the encapsulated yeast by CR3-bearing macrophages.…”
Section: Complement-mediated Effector Mechanisms In Cryptococcal Infementioning
confidence: 99%
“…125 The presence of complement is a prerequisite for TNF-a induction. 125,126 Opsonised C. neoformans also provokes the release of TNF-a from DC. 107 The produced TNF-a efficiently supports ingestion of the encapsulated yeast by CR3-bearing macrophages.…”
Section: Complement-mediated Effector Mechanisms In Cryptococcal Infementioning
confidence: 99%
“…Human peripheral blood monocytes were prepared from the leucocyte concentrate by Ficoll-hypaque density gradient centrifugation and adherence to culture dishes in serum-free Dulbecco's modiÂźed Eagle's minimal essential medium (DMEM). 25 The adherent cells were recovered by scraping and resuspended in RPMI-1640 containing 10% fetal bovine serum (FBS). Cells were preincubated with chloroquine for 2 h before addition of PMA (10 ng/ml).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Rather, we found higher initial (day 7) TNF-α concentrations in mice infected with ST5 isolates, suggesting this genotype elicits a more intense initial inflammatory response. Previous studies have suggested that capsule components, or cryptococcal cells themselves, have a dose-dependent ability to stimulate TNF-α production by various immune effector cells 47,48 . The more robust initial inflammatory response we observed may have been due to the ST5 capsular phenotype.…”
Section: Discussionmentioning
confidence: 99%